AAPM task group 317 report: A joint AAPM and ESTRO report on brachytherapy catheter, needle, and applicator tracking technology - Beaulieu, Luc; Bert, Christoph; Borot de Battisti, Maxence; Cormack, Robert A.; Cunha, J. Adam M.; Damato, Antonio L.; Deufel, Christopher L.; Hautvast, Gilion L.T.F.; Hsu, I. Chow; Kolkman-Deurloo, Inger Karine K.; Moerland, Marinus A.; Niatsetski, Yury; et al. (Medical Physics, 2025)
In recent years, various tracking technologies that work independently of imaging systems have been proposed to automate, simplify, and enhance various tasks in the brachytherapy treatment workflow. These tasks, critical to the overall accuracy of the therapeutic dose delivery, include applicator, catheter and needle insertion guidance, and reconstruction as well as transfer tube connection in afterloading technique. Task Group 317 was established as a joint American Association of Physicists in Medicine (AAPM) and European Society for Radiotherapy and Oncology (ESTRO) committee to review: the current state-of-the-art scientific literature as it pertains to tracking technology in the field of brachytherapy; the benefits and issues related to the use of the technology for automated reconstruction of brachytherapy implants, quality control (QC) tasks such as channel path and tip reconstruction, and real-time guidance tasks; their limitations, in particular in the clinical environment and, finally, to develop recommendations related to commissioning, quality assurance (QA) and clinical use. The Task Group has looked in detail at key tracking technologies in advanced brachytherapy applications: infrared, electromagnetic, fiber optic shape sensing (fiber Bragg grating), and active radiofrequency coil tracking. For each, the performance and accuracy in well-controlled conditions as well as in clinically relevant environments are provided. Guidelines for clinical implementations, including target accuracy and performance needed for critical tasks, are summarized. Risk-based analysis is discussed in the context of an electromagnetic-based tracking system used as part of a clinical trial. The report concludes with the essential elements of an effective quality management program dedicated to the advanced features enabled by the above-described technology.
CRIS-Team Scopus Importer:2025-10-24
Keywords: applicator reconstruction; applicator tracking; brachytherapy; electromagnetic tracking; error detection; fiber Bragg grating; fiber shape sensing; infrared markers; real-time guidance